Governance of Technical Guidance at the Voting Organizing Group (KPPS) level in the 2019 Election in Tebing Tinggi City: Determinants of the Continuity of Democracy - Yessi Sonia Atarini Sinulingga; Iskandar Zulkarnain; Bengkel Ginting (Universitas Medan Area, 2023)
This study aims to describe the Governance of Technical Guidance at the Voting Organizing Group (KPPS) level in the 2019 Election in Tebing Tinggi City as a determinant of the sustainability of democracy. This study used a qualitative type of research, so that researchers could obtain direct and more detailed information from informants by telling the steps taken by the Tebing Tinggi City KPU (General Election Commissions) in conducting technical guidance on KPPS and the impact on participants in Bimtek. This research was conducted at the Tebing Tinggi City KPU, North Sumatra Province in the 2019 Election. The results showed that the KPPS in this case worked according to the capabilities and understanding found from the results of following technical guidance carried out by PPK and PPS in stages. However, the biggest obstacle to KPPS technical guidance in the 2019 elections in Tebing Tinggi City was constrained by several of the following factors, namely: 1. Budget, 2. Time Planning and 3. Technical Guidance Method. Researchers found the most effective formula used, namely the Simulation method in conducting technical guidance on KPPS to make it more effective.